2011
DOI: 10.1016/j.febslet.2011.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Increase in CIP2A expression is associated with doxorubicin resistance

Abstract: Edited by Varda RotterKeywords: Cancerous inhibitor of PP2A Doxorubicin Akt p53 a b s t r a c tThe cancerous inhibitor of protein phosphatase 2A (CIP2A) increases the migration and metastasis of various cancer cells. Overexpression of CIP2A has been shown to increase the proliferation of MDA-MB-231 cells. We thus assessed whether CIP2A expression is associated with sensitivity to doxorubicin. MDA-MB-231 cells showed an increase in CIP2A expression after treatment with doxorubicin, while MCF-7 cells showed a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 24 publications
2
48
0
Order By: Relevance
“…To circumvent the acknowledged limitations in the repeatability of published microarray results (Ioannidis et al, 2009), the reported CIP2A signature consists only of genes regulated by CIP2A depletion in all five independent sample pairs. All tested signature genes were shown by quantitative RT-PCR to be regulated by CIP2A in four cancer cell lines (Figures 1d and 6e and Supplementary Figures 1B and C) in which CIP2A has previously been shown to be overexpressed (Junttila et al, 2007;Come et al, 2009;Khanna et al, 2009;Choi et al, 2011). Thus, we consider the reported CIP2A signature to be a reliable representation of the transcriptional program driven by CIP2A in human cancer cells.…”
Section: Discussionmentioning
confidence: 98%
“…To circumvent the acknowledged limitations in the repeatability of published microarray results (Ioannidis et al, 2009), the reported CIP2A signature consists only of genes regulated by CIP2A depletion in all five independent sample pairs. All tested signature genes were shown by quantitative RT-PCR to be regulated by CIP2A in four cancer cell lines (Figures 1d and 6e and Supplementary Figures 1B and C) in which CIP2A has previously been shown to be overexpressed (Junttila et al, 2007;Come et al, 2009;Khanna et al, 2009;Choi et al, 2011). Thus, we consider the reported CIP2A signature to be a reliable representation of the transcriptional program driven by CIP2A in human cancer cells.…”
Section: Discussionmentioning
confidence: 98%
“…For example, high CIP2A expression predicts poor survival in several types of cancers (10,13,14,36,38). Furthermore, recent reports suggest that CIP2A expression is associated with resistance to several anticancer drugs (14,15,31). Likewise, it has been well established that Plk1 is upregulated in tumors and has been validated as a therapeutic target in many types of cancers (8).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our observations, several lines of evidence have indicated that cell cycle-arresting agents/conditions modulate CIP2A expression in various cancer cells. For example, serum starvation reduces CIP2A expression in gastric cancer cells and doxorubicin treatment reduces it in p53-proficient cells but not in p53-deficient cells (31,32). Moreover, several cell cycle-promoting factors, such as c-Myc and E2F1, have been reported to stimulate CIP2A expression (12,33).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicate that CIP2A may be a molecular determinant of bortezomib's sensitivity in leukemia cells. Recently Choi et al 42 also showed that doxorubicin could down-regulate CIP2A. Therefore, anticancer agents that target CIP2A may be an attractive alternative anti-cancer strategy.…”
Section: Discussionmentioning
confidence: 99%